2017
DOI: 10.1111/maps.12847
|View full text |Cite
|
Sign up to set email alerts
|

A gamma‐ray spectroscopy survey of Omani meteorites

Abstract: The gamma-ray activities of 33 meteorite samples (30 ordinary chondrites, 1 Mars meteorite, 1 iron, 1 howardite) collected during Omani-Swiss meteorite search campaigns 2001-2008 were nondestructively measured using an ultralow background gamma-ray detector. The results provide several types of information: Potassium and thorium concentrations were found to range within typical values for the meteorite types. Similar mean 26 Al activities in groups of ordinary chondrites with (1) weathering degrees W0-1 and lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…Uranium enrichment is the other weathering proxy that has been observed in hot desert meteorites which is suggested to form as a result of contamination by soil fragments and interaction with fluids originating from the soil (e.g., Hezel et al, 2011). As a consequence of these processes, Lu/Hf and Th/U ratios in our analyzed meteorites, in particular in hot desert samples have been Pb isotopic systems which also have been reported by and Weber et al (2017).…”
Section: Samarium-nd Systematicssupporting
confidence: 81%
See 1 more Smart Citation
“…Uranium enrichment is the other weathering proxy that has been observed in hot desert meteorites which is suggested to form as a result of contamination by soil fragments and interaction with fluids originating from the soil (e.g., Hezel et al, 2011). As a consequence of these processes, Lu/Hf and Th/U ratios in our analyzed meteorites, in particular in hot desert samples have been Pb isotopic systems which also have been reported by and Weber et al (2017).…”
Section: Samarium-nd Systematicssupporting
confidence: 81%
“…Observing these effects on a fall meteorite emphasizes the importance of this matter. Isotopic changes caused by meteorite weathering are also reported in H (Stephant et al, 2018), O (Stelzner and Heide, 1996), noble gases (Cartwright et al, 2010;Kaneoka, 1983;Schultz et al, 2005), Sr (Borg et al, 2016(Borg et al, , 2003Brandon et al, 2004;Elardo et al, 2014;Shih et al, 2007), Hf (Sokol et al, 2008;Tatsumoto et al, 1981), Os (Borg et al, 2003;Brandon et al, 2012), Fe (Saunier et al, 2010), U-and Th-series as well as Cs (Weber et al, 2017), and Pb (Tatsumoto et al, 1981) isotopes.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 92%
“…In Oman hot desert meteorite finds, 137 Cs has been detected, but the determined activities were only <0.2 to 10.3 dpm per kg (median 1.25 dpm per kg) and with lower bulk activities in large masses (Weber et al. ). In this context, it should be noted that contamination of 137 Cs likely is concentrated to the exposed surface of meteorites, so activity values obtained with gamma‐ray spectrometry are not fully representative for concentrations in the analyzed bulk material.…”
Section: Discussionmentioning
confidence: 99%
“…Potassium concentrations have often been used as a quality control when assessing the precision of gamma spectrometry measurements on ordinary chondrites (e.g., Weber et al 2017). Occasionally, studies have adopted published average bulk values of K in corresponding chondrite groups for internal standardization.…”
Section: Bulk Potassium In Ordinary and Enstatite Chondritesmentioning
confidence: 99%
“…However, the 14 C method cannot resolve the relative age distribution in the youngest samples, so it has so far been unclear to what extent the least weathered chondrites from Oman represent relatively recent falls and whether the proportion of relatively recent falls within the whole population is consistent with their terrestrial age distribution. Prior studies using gamma-ray spectrometry have identified two meteorites from Oman, SaU 424 (Weber et al, 2017) and SaU 606 (Rosén et al, 2020), that fell during the two decades covered by 22 Na measurements of these studies (~1986-2018). In the present study, we continue the search for chondrites with young terrestrial ages among the least weathered meteorites in the Omani-Swiss meteorite search collection using the previously successful method of estimating terrestrial ages by measuring 22 Na/ 26 Al activity ratios in samples which were so far not analyzed.…”
Section: Introductionmentioning
confidence: 99%